Different patterns of spinal cyclooxygenase-1 and cyclooxygenase-2 mRNA expression in inflammatory and postoperative pain - Procházková, Michaela; Doležal, Tomáš; Slíva, Jiří; Kršiak, Miloslav (Basic & clinical pharmacology & toxicology, 2006)
Levels of cyclooxygenase-2 (COX-2) mRNA, but not those of COX-1, were reported to be raised significantly after peripheral inflammation in the rat spinal cord. The aim of the present study was to ascertain whether this pattern of COX-2 and COX-1 expression applies also to other pain conditions induced by surgical procedure. Experiments were performed on two types of pain models. In a model of postoperative pain, 1 cm longitudinal incision was made through skin, fascia and muscle of the plantar aspect of the right hind paw in anaesthetized rats. In the second model, peripheral inflammation was induced by unilateral, intraplantar injection of carrageenan in the right hind paw. Carrageenan injection or skin incision produced marked and significant reduction of paw withdrawal latencies to noxious radiant heat stimuli after 2 and 6 hr. Under the acute inflammation 2 and 6 hr after carrageenan injection levels of COX-2 mRNA were markedly raised (7.8 and 15.5 times; P<0.001, respectively) while spinal levels of COX-1 mRNA were not significantly altered (n.s.). In contrast, spinal levels of COX-2 mRNA were raised less markedly in a model of postoperative pain (4.9 times at 2 hr; P<0.001 and 2.9 times (n.s.) at 6 hr after surgery) whilst levels of COX-1 mRNA in the lumbar spine were increased significantly (2.3 times; P<0.001) 6 hr after surgery. The present findings indicate that expression of COX-2 mRNA in the spine is less dominant in postoperative pain than in inflammatory pain and that spinal COX-1 mRNA is upregulated in postoperative pain.
Keywords: financování organizované; Animals; Pain, Postoperative; zánět; Pain Measurement; Hindlimb; Rats, Wistar; Spinal Cord; Cyclooxygenase 2; Up-Regulation; mícha; upregulace; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; měření bolesti; Inflammation; RNA, Messenger; Financing, Organized; karagenan; zadní končetina; Male; Reverse Transcriptase Polymerase Chain Reaction; cyklooxygenasa 2; modely nemocí na zvířatech; cyklooxygenasa 1; Disease Models, Animal; krysa rodu Rattus; pooperační bolest; exprese genu; Carrageenan; zvířata; mužské pohlaví; Cyclooxygenase 1; Rats; Gene Expression; potkani Wistar